2020
DOI: 10.1093/intimm/dxaa022
|View full text |Cite
|
Sign up to set email alerts
|

Immune-checkpoint profiles for T cells in bronchoalveolar lavage fluid of patients with immune-checkpoint inhibitor-related interstitial lung disease

Abstract: Immune-checkpoint inhibitors (ICIs) have improved clinical outcomes and are becoming a standard treatment for many cancer types. However, these drugs also induce immune-related adverse events, among which interstitial lung disease (ILD) is potentially fatal. The underlying mechanism of ILD induction by ICIs is largely unknown. With the use of flow cytometry, we determined the expression levels of the immune-checkpoint proteins PD-1, TIM-3, TIGIT, LAG-3 and PD-L1 in T cells of bronchoalveolar lavage fluid (BALF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 34 publications
5
22
0
Order By: Relevance
“…The DAD pattern is characterized by scattered or diffuse areas of groundglass opacities with or without traction bronchiectasis. In our study, 77% OP, 15% HP, and 7.7% NSIP patterns were observed among 13 cases of ICI-pneumonitis [24]. Nishino et al reported 20 cases of ICI-pneumonitis in 10 trials of nivolumab imaging with the following rates: 65% OP, 15% NSIP, 10% HP, and 10% DAD [54].…”
Section: Radiographic Findingssupporting
confidence: 58%
See 2 more Smart Citations
“…The DAD pattern is characterized by scattered or diffuse areas of groundglass opacities with or without traction bronchiectasis. In our study, 77% OP, 15% HP, and 7.7% NSIP patterns were observed among 13 cases of ICI-pneumonitis [24]. Nishino et al reported 20 cases of ICI-pneumonitis in 10 trials of nivolumab imaging with the following rates: 65% OP, 15% NSIP, 10% HP, and 10% DAD [54].…”
Section: Radiographic Findingssupporting
confidence: 58%
“…We previously reported that T-cell-dominated lymphocytosis is evident in bronchoalveolar lavage fluid (BALF) from ICI-pneumonitis [23,24], which is consistent with other case series [25][26][27]. Proportions of CD8 + T cells expressing immunecheckpoint proteins (CD8 + PD-1 + TIM-3 + ), characteristic of tumor-infiltrating T lymphocytes (TILs) [28], are higher in ICI-pneumonitis than in other ICI-associated causes [23,24,29]. These observations suggest that TILs may contribute to the pathogenesis of ICI-ILD.…”
Section: Pathobiology Of Ici-pneumonitismentioning
confidence: 99%
See 1 more Smart Citation
“…Flow cytometry was performed as described previously [ 11 ]. Briefly, BALF was filtered through a mesh to remove debris and centrifuged to isolate cells.…”
Section: Methodsmentioning
confidence: 99%
“…Using bronchoscopy, a deep sputum sample can be collected, which is reliable for elimination of the differential diagnosis of infection and guidance of antimicrobial therapy (21). In ICI pneumonitis, BAL fluid often show lymphocytic inflammation of alveoli with an increased proportion of lymphocytes in the cell count [normal lymphocyte count ≈11%, in ICI pneumonitis ≈37% (22,23)]. Transbronchial biopsies during bronchoscopy can be considered and may be helpful to make the diagnosis (24).…”
Section: Bronchoscopymentioning
confidence: 99%